Meninjau Kembali Fatwa Dakwah Digital di Indonesia Berdasarkan Paradigma Hukum Islam Kontemporer - Islamy, Athoillah; Muhammad Abduh; Eko Siswanto; Mohamad Badrun Zaman (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
The abundance of ideologically charged digital da'wah content often has implications for integration problems amidst the plurality of social life, not only among Muslims themselves, but also social relations with other religious communities. The polemic calls for the importance of digital da'wah paradigms and ethics, both regulated by state norms and religious norms. In this regard, this qualitative study with a normative-philosophical approach aims to identify the paradigm of contemporary maqasid sharia in the fatwa of the Indonesian Ulema Council of East Java Province No. 06 of 2022 on Digital Da'wah Ethics.. The maqasid sharia theory developed by Jasser Auda was used as the theory of analysis. Reduction, presentation, and verification techniques used in data analysis. The results of this study found the development of maqasid sharia value as the basis for the paradigm and ethics of digital da'wah in the provisions of the fatwa, namely the value of hifz 'ird in the importance of humanist and pluralist da'wah content, and The value of hifz waton in the importance of da'wah content that prioritises public conduciveness and nationalism. the importance of developing maqasid fiqh for preachers in the paradigm and ethics of da'wah in the midst of the plurality of social, religious and state life. However, this study has not examined the effectiveness of the fatwa in the field. It is important to study this further.